Religious Aspects of Colombia's La Violencia: Explanations and Implications - Dailey, Suzanne (A journal of church and state, 1973)
Suzanne Dailey; Religious Aspects of Colombia's La Violencia: Explanations and Implications, Journal of Church and State, Volume 15, Issue 3, 1 October 1973, Pa